Chronic Toxicity Effect of Mimosa pudica Leaf Extract Towards Histology Profile of Stomach and Duodenum in Mice - Andayani, Ni Kadek Prederika Sari; Setyawati, Iriani; Sudatri, Ni Wayan (Jurnal Riset Biologi dan Aplikasinya, 2023)
In Indonesia, Mimosa pudica Linn. (M. pudica L.) is a wild plant (weed) from the Mimosaceace family. This plant is widely used as a traditional medicine for various types of diseases such as insomnia, acute eye inflammation, urolithiasis (urinary stones), fever, and bronchitis. This study aimed to find out the effect of M. pudica leaf extract on the histological damage of the stomach and duodenum of mice. This study used a Completely Randomized Design with 24 male mice, which were divided into control placebo (P0) given CMC-Na 0.5%; and M. pudica leaf extract doses of 200 mg/kg body weight (P1); 400 mg/kg body weight (P2); and 600 mg/kg body weight (P3). The extract was administered orally for 28 days. On day 29, the animal was dissected to collect its digestive organs. The histological preparation of the stomach and duodenum of mice was performed by using the paraffin method and Hematoxylin and Eosin staining to observe the histological damage, namely congestion, hemorrhage, epithelial cells desquamation, inflammatory cell infiltration, edema, and hyperplasia. Quantitative data were analyzed with a one-way ANOVA test and Duncan's post hoc test with the SPSS version 22. The results showed that the M. pudica leaf extract increased hemorrhage and hyperplasia damage at doses of 400 and 600 mg/kg body weight in mice’s duodenum.